Lymphocyte antigen 6K signaling to aurora kinase promotes advancement of the cell cycle and the growth of cancer cells, which is inhibited by LY6K-NSC243928 interaction. (1st April 2023) - Selvanesan, Benson Chellakkan; Varghese, Sheelu; Andrys-Olek, Justyna; Arriaza, Ricardo Hernandez; Prakash, Rahul; Tiwari, Purushottam Babu; Hupalo, Daniel; Gusev, Yuriy; Patel, Megha Nitin; Contente, Sara; Sanda, Miloslav; Uren, Aykut; et al.
Abstract: Lymphocyte antigen 6K (LY6K) is a small GPI-linked protein that is normally expressed in testes. Increased expression of LY6K is significantly associated with poor survival outcomes in many solid cancers, including cancers of the breast, ovary, gastrointestinal tract, head and neck, brain, bladder, and lung. LY6K is required for ERK-AKT and TGF-β pathways in cancer cells and is required for in vivo tumor growth. In this report, we describe a novel role for LY6K in mitosis and cytokinesis through aurora B kinase and its substrate histone H3 signaling axis. Further, we describe the structural basis of the molecular interaction of small molecule NSC243928 with LY6K protein and the disruption of LY6K-aurora B signaling in cell cycle progression due to LY6K-NSC243928 interaction. Overall, disruption of LY6K function via NSC243928 led to failed cytokinesis, multinucleated cells, DNA damage, senescence, and apoptosis of cancer cells. LY6K is not required for vital organ function, thus inhibition of LY6K signaling is an ideal therapeutic approach for hard-to-treat cancers that lack targeted therapy such as triple-negative breast cancer. Highlights: Discovery of a unique function for LY6K in mitosis and cytokinesis via aurora B kinase signaling in cancer cells. Structural underpinnings of the interaction between the inhibitor NSC243928 and the protein LY6K. Mechanism of action of small molecule NSC243928 in LY6K signaling. NSC243928 inhibits cell cycle, disrupts mitosis and cytokinesis resulting in DNA damage, senescence, and cancer cell death.